Development of Highly Informative Genome-Wide Single Sequence Repeat Markers for Breeding Applications in Sesame and Construction of a Web Resource: SisatBase - Dossa, Komivi; Yu, Jingyin; Liao, Boshou; Cisse, Ndiaga; Zhang, Xiurong (Frontiers in Plant Science, 2017)
The sequencing of the full nuclear genome of sesame (Sesamum indicum L.) provides the platform for functional analyses of genome components and their application in breeding programs. Although the importance of microsatellites markers or Simple Sequence Repeats (SSR) in crop genotyping, genetics and breeding applications is well established, only a little information exist concerning SSRs at the whole genome level in sesame. In addition, SSRs represent a suitable marker type for sesame molecular breeding in developing countries where it is mainly grown. In this study, we identified 138,194 genome-wide SSRs of which 76.5% were physically mapped onto the 13 pseudo-chromosomes. Among these SSRs, up to 3 primers pairs were supplied for 101,930 SSRs and used to in silico amplify the reference genome together with two newly sequenced sesame accessions. A total of 79,957 SSRs (78%) were polymorphic between the 3 genomes thereby suggesting their promising use in different genomics-assisted breeding applications. From these polymorphic SSRs, 23 were selected and validated to have high polymorphic potential in 48 sesame accessions from different growing areas of Africa. Furthermore, we have developed an online user-friendly database, SisatBase (http://www.sesame-bioinfo.org/SisatBase/), which provides free access to SSRs data as well as an integrated platform for functional analyses. Altogether, the reference SSR and SisatBase would serve as useful resources for genetic assessment, genomic studies and breeding advancement in sesame, especially in developing countries.